Analisis Ujian Keterampilan Berbicara Berdasarkan Kerangka Acuan Umum Eropa (CEFR): Studi Kritis dalam Cahaya Referensi Pendidikan: Taḥlīl Ikhtibārāt Mahārat al-Kalām Wifqa al-Iṭār al-Ūrūbī al-Marjaʿī (CEFR): Dirāsah Naqdiyyah fī Ḍaw’i al-Marājiʿ at-Taʿlīmiyyah - Siti Nur Fadlilah; Ihwan Mahmudi; Fachrina Rahmasari; Rania Izzati; Fasya Asyifauzzahra; Shafwatul Widad (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2025)
This study analyzes the speaking skill tests presented in the book Ikhtibarāt Lughawiyyah by Muhammad Ali Khun, based on the Common European Framework of Reference for Languages (CEFR). The study employed a qualitative methodology using a document analysis approach, with the aforementioned book as the primary source, while CEFR descriptors and relevant literature served as secondary sources. The analysis revealed 17 types of speaking skill tests, including: oral reading, oral questions, oral repetition, sentence transformation, picture description, dialogue, interviews, pronunciation, phoneme tests, map-based questions, free speech, time-telling, substitution, and oral compensation. Among these tests, 6 align with the beginner level (A1–A2), 5 with the intermediate level (B1–B2), while 6 tests do not have a clear classification according to the CEFR. The findings indicate an imbalance between receptive and productive skills, as well as the absence of a clear guideline for matching levels to the CEFR. The study recommends developing tests aligned with the CEFR, achieving balance between language skills, and applying a progression of difficulty levels, in order to enhance communicative competence and linguistic accuracy among learners.